Analysis of mixed convection and hall current for MHD peristaltic transport of nanofluid with compliant wall. (February 2021) - Alsaedi, A.; Nisar, Z.; Hayat, T.; Ahmad, B.
Abstract : Effect of Hall current for mixed convective peristaltic transport of nanoliquid in a compliant wall channel is discussed. Nanoliquid consisting of Brownian motion and thermophoresis saturates the porous space. Partial slip and convective conditions impacts are simultaneously discussed. The problem statements are presented using a small Reynolds number and long wavelength. Numerical computations have been executed for the impacts of various parameters on velocity, temperature, nanoparticles concentration, and heat transfer coefficient are shown and discussed with the help of graphs. We found that velocity and temperature are increasing the function of Hall parameter. Opposite behavior is noticed for Grashof parameters on temperature and concentration.